(untitled) (REGE Revista de Gestão, 2024)
Purpose – Agile methods are increasingly being applied in the contexts of innovation beyond traditionalinformation technology (IT) and physical product development projects, such as when process improvementsare being implemented. Nevertheless, this phenomenon is still recent and little addressed in the literature, withfew descriptions of empirical cases. This study aims to address this gap. Design/methodology/approach – This multiple case study aims to present and discuss the application ofAgile practices embedded in large companies’ innovation value chains, focusing on improvements of businessprocesses. The following research question is pursued: How are large companies applying elements of Agilemethods to their innovation processes when implementing incremental improvements in their operationalprocesses? Based on the idea that the Agile-Stage-Gate model is an alternative to this challenge, this studyinvestigates the application of this hybrid model in two large Brazilian companies by presenting theiridiosyncrasies, lessons learned, adaptations, challenges and benefits. Findings – Overall, it was observed that the experience with the application of the Agile-Stage-Gate model ispositive for these companies, with better customer engagement, easier project control and increasedproductivity of the project team. Originality/value – For those aiming to implement the Agile-Stage-Gate model, this paper identifies the mainadaptations made in order to combine the purist approaches and critical success factors for its implementation.